High Botulinum Toxin‐Neutralizing Antibody Prevalence Under Long‐Term Cervical Dystonia Treatment. Issue 5 (19th May 2016) - Hefter, Harald; Rosenthal, Dietmar; Moll, Marek
Abstract: Background: The aim of this study was to determine the prevalence of neutralizing antibodies in a large cohort of long‐term treated patients with cervical dystonia (CD) still responding to repetitive injections with botulinum toxin (BoNT). Methods: Consecutively recruited CD patients (n = 221) under long‐term BoNT treatment (≥2–21 years) underwent a clinical examination at the same time blood samples were taken for neutralizing antibody determination. Collected data included demographics, mean dose of the last 10 botulinum injections, treatment duration, Tsui score for CD severity, and patients' subjective impression of treatment effect. Blood samples were screened for antibody presence by ELISA; positive samples were further analyzed by mouse hemidiaphragm test. The two laboratories performing antibody testing were blinded to the coded samples. Results: Antibody status could be determined for 212 patients; 39 (18.4%) were ELISA positive and 31 (14.6%) additionally positive in the mouse hemidiaphragm test. Patients with positive neutralizing antibody titers had significantly higher Tsui scores and were treated for a significantly longer time with significantly higher doses. There were no differences between male and female patients and between onabotulinumtoxinA‐ and abobotulinumtoxinA‐treated patients. When BoNT preparations had been switched during the last 10 injections, a significantly higher proportion of neutralizing antibody‐positive patients was detected. Conclusions: Neutralizing antibody prevalence in long‐term treated, still responding CD patients is substantially higher than suggested by follow‐up studies with a shorter time frame. It should therefore be emphasized that antigenicity of BoTN preparations is still a relevant problem and should be taken into account in long‐term treatment decisions.